PERAN HERMENEUTIKA DALAM RANGKA MENINGKATKAN KUALITAS PUTUSAN - Deni Bram (Komisi Yudisial RI, 2011)
ABSTRACTThere are many variables that determine the quality of the judge's decision. The variables could come from the wider community or the environments where the judge socialize and interact. That is why, in making decision, a judge at least, required to absorb the information revealed in the legal facts as much as possible in the courtroom. The inability to absorb the information will make the decision become less ideal and qualified. One method that can be used in order to maximize the quality of a decision is to use the approach of legal hermeneutics in which its relation analyzed in this paper.Keywords: court decision, legal hermeneutics ABSTRAKProfesi hakim tidak dapat dilakukan oleh orang-orang yang panggilan jiwanya hanya sebagai